L’eterno raffreddore di Tarquinia Molza. Natura e storia delle catastrofi nell’opera di Francesco Patrizi da Cherso - Michele Merlicco (Laboratoire Italien)
The process that leads to the degeneration of a body, a political system or any other form of cultural organisation may seem inevitable. Yet, according to Francesco Patrizi da Cherso (1529-1597), there are ways to minimise its consequences. In this contribution, starting with the strange case of the eternal cold of Tarquinia Molza, we will trace the history of the concept of catastrophe in Patrizi’s philosophy, focusing in particular on the different forms of “corruption” that punctuate the life of a single body as much as that of the entire universe. Based on the reading of three texts composed over a period of more than forty years –the Città felice (1553), the Dialoghi della historia (1560) and the Paralleli militari (1594-1595)– we will discover how the conceptual dimension of catastrophe, from Patrizi’s point of view, oscillates between nature, history and myth, and how, in a complicated interweaving of medicine, history and philosophy, Patrizi seeks the conditions for mankind to foresee (and thus, to some extent, control) the unalterable course of nature and adapt to it.